Hepatic‐Targeted Nano‐enzyme with Resveratrol Loading for Precise Relief of Nonalcoholic Steatohepatitis. (9th February 2023) - Tong, Yili; Yu, Xiaofeng; Huang, Yiqin; Zhang, Ziyan; Mi, Lin; Bao, Zhijun
Abstract: Nonalcoholic steatohepatitis (NASH) is characterized by massive lipid deposition in hepatocytes and is often associated with hepatic inflammation and other severe metabolic syndromes. The intervention of NASH can prevent its further progression into hepatocarcinoma. In this study we have successfully constructed liver‐targeted Ce‐based hollow mesoporous nanocarriers loaded with bioactive drugs. This may provide an effective approach for eliminating NASH. Liver‐section‐specific targeting was realized by covalently linked galactose (Gal), which can be specifically recognized by receptors in the membranes of hepatocytes. Meanwhile, resveratrol (Res), a drug used to treat NASH, was efficiently loaded into the pores and cavity of CeO2 (Res@H−CeO2 −Gal). In steatotic HepG2 cells (free fatty acid induction), this nanosystem was found to enhance cellular Res internalization for improved anti‐lipogenesis activity. In mice with NASH, Res@H−CeO2 −Gal increased Res delivery to liver sections for a reduction in lipid accumulation and enhanced anti‐inflammatory activity from the antioxidant capacity of Ce‐based nanocarriers. This effectively recovered NASH mice to the normal state. These findings show that the hepatic targeting and Res delivery nanoplatform could act as a safe and promising strategy for the elimination of NASH and other liver diseases. Abstract : Nonalcoholic steatohepatitis (NASH) causes liver inflammation and other severe metabolic syndromes, and can eventually give rise to hepatocarcinoma. We constructed liver‐targeted Ce‐based hollow mesoporous nanocarriers loaded with bioactive drugs. Liver‐specific targeting was realized by covalently linked galactose (Gal), while resveratrol (Res) was loaded into the pores and cavity of CeO2 (Res@H−CeO2 −Gal). This nanosystem was found to enhance cellular Res internalization for improved anti‐lipogenesis activity. These findings reveal a safe and promising strategy for the elimination of NASH and other liver diseases.